Hyperosmolarity-Induced Cornification of Human Corneal Epithelial Cells Is Regulated by JNK MAPK - Chen, Zhuo (Invest Ophthalmol Vis Sci, 2008)
PURPOSE. To evaluate the effects of hyperosmolar stress on expression of cornified envelope (CE) precursors and transglutaminases (TGs) by primary cultured human corneal epithelial (PCHCE) cells and the regulatory effects of JNK MAPK on this process. METHODS. Expression of CE precursors and TGs were evaluated in PCHCE cells exposed to media of increasing osmolarity (350 – 450 mOsM) for 24, 48, and 72 hours. JNK1 and -2 MAPKs were inhibited by addition of short interfering (si)RNA. Relative levels of mRNA transcripts and proteins were evaluated. TG activity, cell viability, and apoptosis were detected in PCHCE cells, with or without siRNA-JNKs. RESULTS. Exposure of PCHCE cells to hyperosmolar medium increased TG activity at 3 hours, levels of the CE precursors SPRRlb and -2a and membrane-associated TG1 mRNA at 6 hours, and tissue-type TG2 mRNA at 24 hours. Osmotic stress decreased corneal epithelial cell viability, which was due in part to stimulation of apoptosis and cornication death. Inhibiting JNK2 production by siRNA in osmotically stressed PCHCE cells prevented the stimulation of SPRR and membrane-associated TG1 production and TG activity, and improved cell viability, whereas inhibition of JNK1 prevented early apoptosis. CONCLUSIONS. Osmotic stress promotes production of certain CE proteins and cross-linking membrane-associated TG1 and decreases cell viability via JNK MAPK-mediated pathways. Strategies that inhibit JNK production downregulate the cornification response of PCHCE cells to osmotic stress. These findings have potential therapeutic implications for preventing cornification of the corneal epithelium in response to the hyperosmolar tear film in dry eye disease.